Arahan Kebijakan Untuk Mengurangi Dinamika Penggunaan Lahan pada DAS Antokan, Provinsi Sumatera Barat - Umar, Iswandi (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2021)
The need for land has increased every year, and this increase is caused by the rate of population growth, resulting in changes in land use. Uncontrolled land use conversion has led to catastrophic flooding in the Antokan watershed. The purpose of this study was to determine the direction of land use change policies in the Antokan Watershed, West Sumatra Province. To determine land use change using the GIS method with the overlay technique of land use maps for the period 2000-2020. Furthermore, to determine the policy direction using the ISM method involving 20 experts. Research results in the Antokan watershed have shown changes in land use of 4,178 hectares during the 2000-2020 period. Changes occur in forest areas, mixed gardens, shrubs, and rice fields which have decreased, on the other hand, settlements, plantations and open land have expanded. Furthermore, there are two sub-elements that are the priority for policy direction to reduce the rate of land use change, namely making regulations and firm sanctions on land use errors (E3) and consistency in enforcing land use laws (E4).